Influence of synthesis conditions on structural properties of MCM-48 - Taralkar, U. S.; Kasture, M. W.; Joshi, P. N. (Journal of Physics and Chemistry of Solids, 2008)
The influence of synthesis variables such as time, cetyltrimethyl ammonium hydroxide (CTAOH) concentration, water content, pH, temperature and silica source on the structural properties of Si-MCM-48 is investigated. Time-dependent studies on the progressive development of MCM-48 have indicated that synthesis time is a crucial parameter, which influences the unit cell parameter. The formation of different mesophases was observed when the concentration of CTAOH and pH of the initial gel were varied. The Si-29 MASNMR results showed that the (Q(2) +W-3)/Q(4) ratio decreases with the increase in synthesis temperature. On account of increase in W units at high-temperature synthesis run, Si-MCM-48 with highly polymerized silica walls with lower surface area was obtained when compared with Si-MCM-48 prepared at lower temperature. Such effect was not significant when Si-MCM-48 was synthesized at the same temperature but using silica sol as a source in place of fumed silica. (c) 2008 Elsevier Ltd. All rights reserved.

Influence of zeolitic structure on photoreduction property and hydrogen evolution reaction - Chatti, Ravikrishna V.; Dubey, Nidhi; Joshi, Meenal V.; Labhsetwar, Nitin K.; Joshi, P. N.; Rayalu, Sadhana S. (International Journal of Hydrogen Energy, 2010)
A new photocatalytic material developed by supporting TiO(2) in combination with transition metal ion like cobalt and heteropolyacid (HPA) on the surface is facilitating enhanced photoreduction of water and methyl orange Zeolites being a solid acid play an important role in the electron transfer reaction, facilitated by the Lewis acid sites in the form of aluminium ions In the present work, four different zeolite matrices namely, NaY zeolite, ultrastable zeolite Y, beta zeolite and titanium silicate-1 have been used for the synthesis of new photocatalytic materials These materials have been evaluated for water splitting by an initial screening procedure using methyl orange photoreduction The photocatalyst containing Na Y has emerged as a potential photocatalyst with hydrogen evolution rate of 2730 mu mol/h/g of TiO(2) Hydrogen evolution was not observed for the composite photocatalysts synthesized using the other zeolite matrices It has been observed that physicochemical properties like Si/Al ratio, acidity and basicity of the zeolite support have a tremendous influence on the photoreduction property of these zeolite matrices (C) 2010 Professor T Nejat Veziroglu Published by Elsevier Ltd All rights reserved
Keywords: H(2) evolution; Lewis acidity; Si/Al ratio; water splitting; Zeolite structure

Influence of Al3+ insertion in the stannosilicate MFI framework on the catalytic performance in vapor phase aniline N-methylation - Niphadkar, P. S.; Joshi, P. N.; Deshpande, Suvarna S.; Bokade, Vijay V. (Applied Catalysis A-General, 2011)
Silica-based Sn-MFI, Al-MFI and Al-Sn-MFI molecular sieves were synthesized by hydrothermal crystallization of gels having molar compositions SiO2:xSnO(2):yAl(2)O(3):0.23 (TPA)(2)O:35H(2)O, where x ranges from 1/0 to 1/200 and y from 1/0 to 1/400. Keeping molar Si/(Al + Sn) = 50, the amount of tin and aluminum in hydrogel was varied (Sn:Al molar ratios = 1:0, 1:0.33, 1:1, 1:3, 0:1) to investigate the synergy between Lewis and Bronsted acid sites in acid catalyzed aniline N-methylation reaction. Catalyst characterization was done by Powder X-ray diffraction, DRUV-vis spectroscopy, temperature programmed ammonia desorption (TPAD) and FTIR spectroscopy. An increase in the Al3+ insertion in Sn-MFI framework resulted in the increase in the stronger acid sites. Al-Sn-MFI showed higher aniline conversion than their monometallic counterparts. A sample having B/L ratio in between 0.67 and 0.91 was found to be optimum for maximizing the NMA yield, indicating the existence synergistic properties of Al-Sn-MFI. Upon process parameter optimization, the optimum sample M50 [Si/Al = 50.2, Si/Sn = 93.8, Si/(Al + Sn) = 43.2] showed the maximum aniline conversion (67%) and NMA selectivity (81%) at reaction temperature = 220 degrees C, weight hourly space velocity (WHSV) = 3 h(-1), molar ratio (aniline to methanol) = 1:8 and TOS = 4 h. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Al-Sn-MFI; Aniline; Bronsted and Lewis acid; Methanol; N-methylaniline